Judicial decisions regarding cancer appeals: an analysis of arguments of the Law as applied to health - Robson Nogueira Costa Santos; Roseney Bellato; Laura Filomena Santos de Araújo; Karla Beatriz Barros de Almeida (Universidade Federal de Goias, 2014)
The implications of developing cancer demand that affected individuals and their families seek professional care, which are not always offered in a manner adequate to their needs. This leads them to appeal to court instances in order to guarantee their right to health. The goal of the present study is to analyze legal struggles in relation to the health of people with cancer. It is a qualitative documentary study analyzing 34 court rulings relative to the period of May 2008 to April 2009, made by the Mato Grosso Court of Justice (TJMT). Out of these, 88.2% were requests for medication, 11.7% for nutritional supplies, 2.9% for land transportation and 2.9% for neurosurgery. Throughout the analysis, we realized that the arguments used by the State were insufficient before those presented by the magistrate used to reaffirm the right to life as guaranteed by the constitution, which takes precedence over interests of the State. doi: 10.5216/ree.v16i2.24577.